Assessing Quality Defects in Frozen Cooked Skipjack Loin Using Seven Tools and Statistical Quality Control - Mubarok, Ahmad S.F.Q.R.; Bancin, Cindy Maria; Khoiriyah, Romyun Alvi; Kusuma, Bayu; Ma’rifat, Tian Nur; Yufidasari, Hefti Salis; Perdana, Angga Wira (JFMR (Journal of Fisheries and Marine Research), 2025)
Quality control is a vital process to ensure that products consistently meet established standards and maintain customer satisfaction. This study examines the implementation of quality control methods in the production of frozen cooked skipjack loin, a key product in the canning and freezing fish industry. Beyond compliance with quality assurance systems such as Good Manufacturing Practice (GMP) and Hazard Analysis and Critical Control Points (HACCP), the industry must adopt rigorous quality control approaches to minimize product defects. Using the Seven Tools of Quality—namely the fishbone diagram, check sheet, Pareto diagram, and control charts—this research aimed to identify major sources of product defects and evaluate quality performance. The analysis revealed several types of recurring defects, with one particular defect being significantly dominant. Furthermore, control chart analysis indicated that the product quality was outside the acceptable control limits, signaling the presence of systematic issues in the production process. These findings highlight the importance of continuous quality improvement efforts to ensure product consistency and excellence.